If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -7x = 7x + -103 Reorder the terms: 9 + -7x = -103 + 7x Solving 9 + -7x = -103 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + -7x + -7x = -103 + 7x + -7x Combine like terms: -7x + -7x = -14x 9 + -14x = -103 + 7x + -7x Combine like terms: 7x + -7x = 0 9 + -14x = -103 + 0 9 + -14x = -103 Add '-9' to each side of the equation. 9 + -9 + -14x = -103 + -9 Combine like terms: 9 + -9 = 0 0 + -14x = -103 + -9 -14x = -103 + -9 Combine like terms: -103 + -9 = -112 -14x = -112 Divide each side by '-14'. x = 8 Simplifying x = 8
| -2+9=5+2n | | 75+e=850 | | 26+5x-6=8x+2 | | -100+x^2= | | 8-2(r-2)=11 | | 7(-3y+2)=8+(3y-2) | | 5(a+3)=3a-7 | | 8(3-4k)= | | 2y^2=10y | | 5-3z-118=z-1+8z | | 5d+d+6d+2=4d | | -3(d+7)=5d | | -1.2x-(2+9x)=-18+1.8x | | x+1+2x=91 | | 12+6x-20=54 | | 1000+t=4318 | | 5(9k-2)= | | 1(x+11)=-2(8-x) | | 1000+t=4310 | | y=-6+4x+2x^2 | | 8(5-h)= | | 51=7(-1+2u)+2 | | -4(n+2)-2n=28 | | 4(7-3x)= | | 6x-1=24 | | -151=24-30n+5 | | 2(1.4)-(-4)/5=-2 | | 10-3x=21 | | 3y^3-13y-10=0 | | 5(x+5)=7(1+x) | | 2(4-2s)=-2(r+5) | | 6(2f-7)= |